Shallow-water lee-side waves at obstacles: Experimental characterization and turbulent non-hydrostatic modeling using weighted-averaged residual equations. (September 2022) - Gamero, Pedro; Cantero-Chinchilla, Francisco N.; Bergillos, Rafael J.; Castro-Orgaz, Oscar; Dey, Subhasish
Abstract: The flow over uneven topography is a problem of interest in environmental fluid flow modeling, including flows over river bedforms, exchange flows over oceanic sills or the airflow over mountains. The common experimental procedure to investigate these flows, moving a small obstacle in a laboratory flume, yields experimental difficulties, whereas modeling using non-linear shallow flow equations does not explain all the flow phenomena. Novel alternative procedures are presented for the experimentation and shallow water representation of flow interaction with obstacles. A large-scale obstacle model is constructed in a dam-break set-up, and used to generate flow phenomena over topography, including dispersive and broken surges, wave reflection, hydraulic jumps and non-hydrostatic sill overflows. Simulations are conducted with a shallow-water weighted-averaged residual flow software for turbulent flows. The proposed software reproduces the experiments satisfactorily, supporting its use in modeling, whereas the new experimental database can be used by modelers to test their software. Highlights: A novel experimental procedure to study wave interaction with obstacles is presented. A new experimental database of utility for software validation by environmental fluid flow modelers is generated. A new weighted-averaged residual flow software for turbulent flow over obstacles is presented.